2020
DOI: 10.1007/s00266-020-01868-y
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding a Second Wave of Medical Errors: The Importance of Human Factors in the Context of a Pandemic

Abstract: The COVID-19 pandemic has had an unprecedented impact on the delivery of healthcare services around the globe. This has resulted in important loss of life for our communities, including health professionals that have been exposed to the disease in their workplace. A human factors approach to the recent changes introduced due to the pandemic can help identify how we can minimize the impact of human error in these circumstances. We hereby present a case study illustrating the application of human factors in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…As evidence has shown for some time, when humans are caught in a cycle of anxiety, fatigue, and stress, errors are more likely to occur ( Stocking et al, 2021 ; Tejos et al, 2020 ). In a study of critical care nurses that concluded just a few months before the onset of the pandemic, Melnyk et al (2021) found that critical care nurses who reported lower physical and mental health, presence of depressive and anxiety symptoms, and low professional quality of life had a 31% to 62% higher likelihood (odds ratio) of having made medical errors than nurses with better health and a higher professional quality of life.…”
Section: Healthcare Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…As evidence has shown for some time, when humans are caught in a cycle of anxiety, fatigue, and stress, errors are more likely to occur ( Stocking et al, 2021 ; Tejos et al, 2020 ). In a study of critical care nurses that concluded just a few months before the onset of the pandemic, Melnyk et al (2021) found that critical care nurses who reported lower physical and mental health, presence of depressive and anxiety symptoms, and low professional quality of life had a 31% to 62% higher likelihood (odds ratio) of having made medical errors than nurses with better health and a higher professional quality of life.…”
Section: Healthcare Deliverymentioning
confidence: 99%
“…Alarms and changes in patient condition went unnoticed due to isolation constraints and were linked to falls and self-extubation, and limited repositioning of COVID-19 patients led to pressure injuries. Tejos et al (2020) describe an incident where a laboratory specimen was mislabeled by a junior nurse who had worked several extra shifts to cover for colleagues who had to quarantine. A culture of safety depends on an organizational climate that creates an atmosphere where staff feels supported and encouraged to report safety issues and concerns ( Alagha et al, 2021 ).…”
Section: Healthcare Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…17 Fatigue and stress are well documented contributing factors to medical errors. 18 Real-time data analytics, combined with a highly customisable reporting structure, can support the delivery of high-quality care and reduce the cognitive load on staff, for example, using a ‘FASTHUG’ 19 report to confirm the presence of EHR orders for feeds, analgesia, sedative infusions, thromboembolism prophylaxis, stress ulcer prophylaxis and glucose control for each patient.…”
Section: Data Analyticsmentioning
confidence: 99%
“… 11 Rapidly changing directives, high stress environments, and fatigue are all factors that can contribute to an increased risk of error. 12 , 13 As part of the hospital‐wide COVID‐19 preparedness plan, the Radiation Oncology Department adopted workflow changes to reduce the number of personnel required to be in hospital to perform their duties. For physicians, this meant a drastically reduced number of in‐person patient assessments, even for new consults.…”
Section: Introductionmentioning
confidence: 99%